2018
DOI: 10.2134/cftm2018.03.0018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulfur and Calcium Source on pH, Anthracnose Severity, and Microdochium Patch Management on Annual Bluegrass in Western Oregon

Abstract: Core Ideas Increasing sulfur application rates reduced the number of fungicide applications required to manage Microdochium patch. Increasing sulfur application rates increased anthracnose severity. Calcium carbonate, calcium sulfate, and calcium phosphate did not have an effect on Microdochium patch or anthracnose severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Iron sulfate applications are known to decrease soil pH (Carrow, Waddington, & Rieke, 2001), and pH has been demonstrated to affect the growth of Microdochium nivale (Bennett, 1933). Previous field trials have also demonstrated that acidifying products, fertilizers and sulfur fungicides can suppress Microdochium patch and lead to a lower soil pH (Brauen, Goss, Gould, & Orton, 1975;Mattox et al, 2016) or reduce the number of fungicide applications (McDonald, Mattox, Gould, & Kowalewski, 2018). With the effects of pH on T A B L E 1 Effects of 97.6 kg FeSO 4 ⋅7H 2 O ha −1 applied at different water carrier volumes and non-treated control (NTC) on turfgrass quality ratings on an annual bluegrass putting green in Corvallis, OR.…”
Section: Microdochium Patch Suppressionmentioning
confidence: 99%
“…Iron sulfate applications are known to decrease soil pH (Carrow, Waddington, & Rieke, 2001), and pH has been demonstrated to affect the growth of Microdochium nivale (Bennett, 1933). Previous field trials have also demonstrated that acidifying products, fertilizers and sulfur fungicides can suppress Microdochium patch and lead to a lower soil pH (Brauen, Goss, Gould, & Orton, 1975;Mattox et al, 2016) or reduce the number of fungicide applications (McDonald, Mattox, Gould, & Kowalewski, 2018). With the effects of pH on T A B L E 1 Effects of 97.6 kg FeSO 4 ⋅7H 2 O ha −1 applied at different water carrier volumes and non-treated control (NTC) on turfgrass quality ratings on an annual bluegrass putting green in Corvallis, OR.…”
Section: Microdochium Patch Suppressionmentioning
confidence: 99%
“…These effects may be aggravated in the colder months of the winter when daylengths are shorter and temperatures are lower (Vargas & Turgeon, 2004). Because S and mineral oil tank mixtures were shown to consistently reduce turfgrass quality and S applications have been tied to other issues such as an increase in the risk of anthracnose (McDonald et al, 2018) or the development of black layer (Berndt & Vargas, 2008), these data suggest that tank mixtures of mineral oil and S are not an effective means of suppressing Microdochium patch while maintaining acceptable turfgrass quality. The green cover percentage differences was greater in the 1st year of the experiment (2015)(2016) than in the 2nd year (2016)(2017) for the rotations that included mineral oil tank mixed with either S or H 3 PO 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Current fungicide application intervals recommended for turfgrass management vary, with typical fungicide labels listing an interval between 7 and 28 d (Clarke et al., 2019). Potential advantages of increasing the time between alternative applications of the same rate include decreasing the total cost of product and labor application costs, decreasing the environmental impact compared to more frequent applications (Kovach et al., 1992), reducing exposure to pesticides by pesticide handlers (Environmental Protection Agency, 2020), and decreasing the total S applications, which decreases the risk of anthracnose on annual bluegrass putting greens (McDonald et al., 2018) and the development of black layer (Berndt & Vargas, 2008). Potential disadvantages would be the lack of complete disease suppression by 3‐wk applications that may not meet golfer expectations (Walsh, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests when S applications reduced the soil pH from 6.3 to 5.3, there was a trend in the reduction of top and root growth of annual bluegrass (Sprague & Burton, 1937). Other research has demonstrated that monthly S applications of 12.3 kg S ha −1 or greater led to an increase in anthracnose ( Colletotrichum cereale Manns sensu lato Crouch, Clarke, & Hillman) severity on an annual bluegrass research green in western Oregon compared to no S additions (McDonald et al, 2018).…”
Section: Introductionmentioning
confidence: 99%